Active commuting and cardiovascular risk among health care workers - Lerssrimongkol, C; Wisetborisut, A; Angkurawaranon, C; Jiraporncharoen, W; Lam, KBH (Oxford University Press, 2016)
Background Although the benefit of physical activity on cardiovascular health has been well demonstrated, being physically active can be difficult for health care workers. Active commuting such as walking or cycling may be a good way to promote physical activity.